Correlating the Structural and Photophysical Properties of Ortho, Meta, and Para‐Carboranyl–Anthracene Dyads. (23rd June 2020) - Marsh, Adam V.; Dyson, Matthew J.; Cheetham, Nathan J.; Bidwell, Matthew; Little, Mark; White, Andrew J. P.; Warriner, Colin N.; Swain, Anthony C.; McCulloch, Iain; Stavrinou, Paul N.; Meskers, Stefan C. J.; Heeney, Martin
Abstract: The role of the carborane isomer is investigated on the structural and photophysical properties of molecules comprising a carborane cluster and a conjugated organic moiety is investigated by synthesizing isomeric o ‐, m ‐, and p ‐carboranyl‐anthracene donor–acceptor dyads. While appending a carborane leads to emission from a low energy intramolecular charge transfer state for the o ‐isomer, as well as emission from an excited state localized on the anthracene, this is not the case for the m ‐ and p ‐carborane derivatives. This difference is attributed to a lower electron affinity for the latter two isomers. However, adding both m ‐ and p ‐ deforms the aromatic backbone and increases its structural rigidity, reducing non‐radiative decay pathways and hence enhancing photoluminescence quantum efficiency relative to anthracene. Abstract : The attachment of isomeric ortho, meta, and para ‐carboranes onto an anthracene core is reported. A strong dependence of the structural and photophysical properties on the nature of the isomer is found, with the only the ortho ‐carborane emitting from a low energy intramolecular charge transfer state, whilst meta ‐ and para ‐carboranes isomers show strong emission from an excited state localised on anthracene .